Structural characterization and impedance studies of PbO nanofibers synthesized by electrospinning technique - Hari Prasad K.; Vinoth S.; Jena P.; Venkateswarlu M.; Satyanarayana N. (My University, 2025)
One-dimensional electrospun lead oxide nanofibers synthesized by a simple electrospinning technique. The prepared lead oxide nanofibers investigated by using TG/DTA, FTIR, Raman, X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analyzer, scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM-EDX), atomic force microscopy (AFM), Transmission electron microscopy (TEM), and impedance spectroscopy techniques. TG/DTA results confirmed the thermal behavior of the as-spun nanofibers. XRD, FTIR, and Raman spectra results, respectively, confirm the formation of pure orthorhombic crystalline phase and structural coordination of the lead oxide (β-PbO) nanofibers. The BET specific surface area of β-PbO nanofibers sample is found to be 51.23 m2 g−1. SEM and AFM micrographs showed the formation of β-PbO nanofibers with a diameter of 85–300 nm. The impedance measurements of lead oxide nanofibers as a function of temperature, 25–150 °C, was evaluated by analyzing the measured impedance data using the winfit software. The electrical conductivity of the lead oxide (β-PbO) nanofibers evaluated by analyzing the measured impedance data using the winfit software is found to be 5.68 × 10−6 S cm−1 at 150 °C. Also, an activation energy (Ea) for the migration of the charge carrier evaluated from the temperature dependence of conductivity plot is found to be 0.27 eV. The temperature dependence AC conductivity of β-PbO nanofibers was evaluated using the measured impedance data and sample dimension. The observed variation of high-frequency AC conductivity attributed to the hopping electrons between the adjacent sites. © 2017 Elsevier B.V.